Management and mitigation of vibriosis in aquaculture: Nanoparticles as promising alternatives - Kah Sem, Nuan Anong Densaad; Abd Gani, Shafinaz; Chong, Chou Min; Natrah, Ikhsan; Shamsi, Suhaili (MDPI, 2023)
Vibriosis is one of the most common diseases in marine aquaculture, caused by bacteria belonging to the genus Vibrio, that has been affecting many species of economically significant aquatic organisms around the world. The prevention of vibriosis in aquaculture is difficult, and the various treatments for vibriosis have their limitations. Therefore, there is an imperative need to find new alternatives. This review is based on the studies on vibriosis, specifically on the various treatments and their limitations, as well as the application of nanoparticles in aquaculture. One of the promising nanoparticles is graphene oxide (GO), which has been used in various applications, particularly in biological applications such as biosensors, drug delivery, and potential treatment for infectious diseases. GO has been shown to have anti-bacterial properties against both Gram-positive and Gram-negative bacteria, but no research has been published that emphasizes its impact on Vibrio spp. The review aims to explore the potential use of GO for treatment against vibriosis.